Eine frühkaiserzeitliche Grubenverfüllung aus dem Hanghaus 2 in Ephesos - Ladstätter, Sabine (Holzhausen, 2020)
In the early Roman imperial period, the remains of an opulent banquet were filled in a pit in Hanghaus 2 of Ephesus. By evaluating the thousands of artifacts and biogenic material, it was possible to reconstruct the feast behind it and to provide a conclusive assumption for its cause. Most likely, it has to be understood as a Cena Publica in honor of a son who was introduced to adult life by putting on the Praetexta toga.